2019
DOI: 10.1177/0300060519827191
|View full text |Cite
|
Sign up to set email alerts
|

Combination of apatinib mesylate and second-line chemotherapy for treating gastroesophageal junction adenocarcinoma

Abstract: Objective To investigate the safety and efficacy of acitinib mesylate combined with chemotherapy in the treatment of patients with gastroesophageal junction adenocarcinoma. Methods A total of 119 patients with gastroesophageal junction adenocarcinoma were enrolled and randomized into an experimental group (n = 60) and a control group (n = 59). Both groups were treated with a combination of taxane, irinotecan and fluorouracil, while the experimental group also received acitinib mesylate. The clinical efficacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Another prospective cohort study found that the addition of apatinib to chemotherapy promotes DCR and PFS compared with chemotherapy alone, and independently correlates with less disease progression after multivariate adjustment as a second-or later-line therapy in GC/GEJAC (23). Furthermore, a randomized controlled study showed that apatinib plus second-line chemotherapy achieved a better DCR, PFS, and OS, as well as fewer adverse events compared to chemotherapy alone in patients with advanced GEJAC (24). In our study, the numerical ORR, DCR, and PFS in both groups were in line with previous studies, while the OS was numerically longer (median OS of 9.0 months in the IG group and 9.4 months in the CG group) compared with that in previous studies that used chemotherapy alone [median OS of 5.2 months in the COUGAR-02 study (docetaxel), 7.4 months in the RAINBOW study (paclitaxel), and 8.3 months in the Keynote-061 study (paclitaxel)] (11,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective cohort study found that the addition of apatinib to chemotherapy promotes DCR and PFS compared with chemotherapy alone, and independently correlates with less disease progression after multivariate adjustment as a second-or later-line therapy in GC/GEJAC (23). Furthermore, a randomized controlled study showed that apatinib plus second-line chemotherapy achieved a better DCR, PFS, and OS, as well as fewer adverse events compared to chemotherapy alone in patients with advanced GEJAC (24). In our study, the numerical ORR, DCR, and PFS in both groups were in line with previous studies, while the OS was numerically longer (median OS of 9.0 months in the IG group and 9.4 months in the CG group) compared with that in previous studies that used chemotherapy alone [median OS of 5.2 months in the COUGAR-02 study (docetaxel), 7.4 months in the RAINBOW study (paclitaxel), and 8.3 months in the Keynote-061 study (paclitaxel)] (11,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials indicated that apatinib alone or combined with chemotherapy was effective and safe for treating advanced EC. [5155] In addition, other clinical trials have confirmed the synergistic effect of low-dose apatinib combined with camrelizumab. [5659] Apatinib may be an option for the treatment of advanced EC.…”
Section: Targeted Drugs Of Ecmentioning
confidence: 99%
“…Combination therapy significantly improved progression-free survival (PFS) and disease control rate (DCR) [12] . Apatinib combined with chemotherapy also demonstrated improved survival benefit in two other studies [13,14] . However, phase 1 dose-escalation studies of apatinib combined with chemotherapy are lacking.…”
mentioning
confidence: 92%